2021
DOI: 10.15376/biores.16.3.4704-4715
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the nutrient contents of leaves, bark, and wood of Persian oak trees (Quercus brantii) affected by decline

Abstract: Tree decline is a physiological phenomenon resulting from climatic disturbances that involves damage to forest ecosystems. This study examined the effects of tree decline on nutrient concentrations in the leaves, bark, and wood of Persian oak (Quercus brantii) trees. Trees were categorized by decline severity (healthy, slight, moderate, and severe decline). Leaves were collected from the middle and outer parts of the crowns. Bark and wood samples were taken at breast height (1.3 m). The contents of Mg, Ca, P, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The Ca, K, and Mn contents reported in this study were approximately of the same order of magnitude as those reported in other studies. Mohammadzadeh et al [ 52 ] found substantially lower K and Ca contents in Quercus brantii sapwood than in the present study and other studies ( Table 2 ). Nutrient content in trees is often strongly related to the pool of available elements in the soil [ 53 , 54 ].…”
Section: Discussioncontrasting
confidence: 53%
“…The Ca, K, and Mn contents reported in this study were approximately of the same order of magnitude as those reported in other studies. Mohammadzadeh et al [ 52 ] found substantially lower K and Ca contents in Quercus brantii sapwood than in the present study and other studies ( Table 2 ). Nutrient content in trees is often strongly related to the pool of available elements in the soil [ 53 , 54 ].…”
Section: Discussioncontrasting
confidence: 53%
“…The binding of tannins to collagens is dependent on temperature, pH, and the molecular weight of the tannins. Therefore, it controls bacterial growth, avoids bad odors, and makes the leather stronger [14,61]. Tannins react with the basic groups of protein in the leather matrix [58].…”
Section: 𝑪𝑶𝑶 𝑷 𝑵𝑯mentioning
confidence: 99%
“…Many minerals, particularly nitrogen, sulfur, and calcium, form part of its organic structure. However, other minerals may be present simply because they are absorbed as ions along with soil water and tend to accumulate as dissolved or stored ionic substances or as precipitates in tissue [60,61]. The cases of Pinus patula, Pinus pseudostrobus, and Pinus rudis present secondary ions of minerals in the analyzed tannic extracts.…”
Section: Scanning Electron Microscopy (Sem) Analysismentioning
confidence: 99%
“…Drought has a great impact on plant nutrients through its effect on water-soil-plant relations (Graciano et al 2005;Sardans et al 2008a). There are several reports indicating the effects of water stress on nutrients in forest trees (Sardans et al 2008a,b;Mohammadzadeh et al 2021;. Drought can change the absorption of elements through processes such as reducing the soil moisture content, affecting the properties of the soil and the activity of soil enzymes, reducing plant growth, and changing the status of plant photosynthesis and metabolism and its ability to acquire nutrients (Sardans et al 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…In various studies, different organs have been selected to examine the status of elements. Some researchers have investigated the elements in the wood and bark of the tree trunk (Mohammadzadeh et al 2021), while others have investigated the nutrient status in leaves, bark, and soil (Sardans and Penuelas 2007;Sardans et al 2008a). In this research, the tree root has been selected as one of the important organs of the tree that has a direct relationship with the soil and has the task of absorbing water and nutrients, and the status of nutrients and how their concentration changes in the root have been compared with the leaves of Persian oak trees, and at the same time, these comparisons have been made between healthy and declining trees.…”
Section: Introductionmentioning
confidence: 99%